Трудовое обучение как средство социализации и адаптации школьников в процессе включения их в производственные отношения в условиях социума - Торопчин, С.И. (My University, 2013)
One of the priority directions of the special (correctional) education of children with deviations in development, along with the General education is to ensure for them a real opportunity to obtain employment training, which allows students to adapt to the labour market. The author of the article acquaints with its own method of teaching of vocational labour training through training before a meta-technology and extra-curricular activities. The author demonstrates the possibility of the implementation of the socialization of the students on specific examples from the teacher's practice.